Pengaruh Work Family Conflict, Beban Kerja, dan Stres Kerja Terhadap Kinerja Guru Wanita SMA Muhammadiyah 1 Sragen - Ajeng Dyah Pramesti; Riska Fii Ahsani (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2024)
This study aims to analyze the significance of the influence of work family conflict, workload, and work stress on the performance of female teachers of SMA Muhammadiyah 1 Sragen. This study used a survey method conducted on female teachers of SMA Muhammadiyah 1 Sragen. Data collection in this study used a questionnaire distributed to respondents. The population in this study, namely all female teachers of SMA Muhammadiyah 1 Sragen which amounted to 31 teachers. The sample in this study amounted to 31 female teachers using the census method. The study used instrument tests and classical assumption tests. Data analysis techniques used in this study used descriptive analysis, multiple linear regression analysis, t test, F test, and coefficient of determination (R2). The validity and reliability test results show that the variables of work family conflict, workload, work stress, and teacher performance are valid and reliable. The results of the classical assumption test show that all classical assumption tests pass. The results of this study obtained a regression equation, namely Y = 19.239 - 0.071 X1 + 0.596 X2 - 0.199 X3. The results of the t test show that the variables of work family conflict and work stress do not have a significant effect on the performance of female teachers of SMA Muhammadiyah 1 Sragen. The results of the F test indicate that the model used to test the effect of work family conflict variables, workload, work stress, and teacher performance is appropriate. The coefficient of determination (R2) = 0.300, meaning that the magnitude of the contribution of the independent influence of work family conflict, workload and work stress on teacher performance is 30%.